2017
DOI: 10.3892/ijmm.2017.3275
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution metabolomics determines the mode of onset of type 2 diabetes in a 3-year prospective cohort study

Abstract: Type 2 diabetes mellitus (DM) is a progressive disease and the rate of progression from non-diabetes to DM varies considerably between individuals, ranging from a few months to many years. It is important to understand the mechanisms underlying the progression of diabetes. In the present study, a high-resolution metabolomics (HRM) analysis was performed to detect potential biomarkers and pathways regulating the mode of onset by comparing subjects who developed and did not develop type 2 DM at the second year i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Although the clear relationships between phospholipids and T2DM have not been elucidated, current studies suggest that the change in phospholipids may be an early factor in the pathogenesis of T2DM. Lee Y et al [ 80 ] found that the cholesterol biosynthetic pathway was important in the development of T2DM. The T2DM group had a higher cholesterol level.…”
Section: Advances In the Pathogenesis Of T2dm Based On Metabonomicmentioning
confidence: 99%
“…Although the clear relationships between phospholipids and T2DM have not been elucidated, current studies suggest that the change in phospholipids may be an early factor in the pathogenesis of T2DM. Lee Y et al [ 80 ] found that the cholesterol biosynthetic pathway was important in the development of T2DM. The T2DM group had a higher cholesterol level.…”
Section: Advances In the Pathogenesis Of T2dm Based On Metabonomicmentioning
confidence: 99%
“…Therefore, untargeted metabolomics provides a unique opportunity to discover new biomarkers (34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
“… 31 Among them, the cholesterol synthesis pathway occupies an important position in T2D. 32 Both systemic and local lipid metabolisms are altered. 6 Li et al used gas chromatography/time-of-flight mass spectrometry (GC´GC-TOFMS) combined with pattern recognition to analyze the plasma of diabetic patients and normal people in a control experiment.…”
Section: Application Of Metabolomicsmentioning
confidence: 99%